2018
DOI: 10.1039/c8ce00877a
|View full text |Cite
|
Sign up to set email alerts
|

Structural diversity, magnetic properties, and luminescence sensing of five 3D coordination polymers derived from designed 3,5-di(2′,4′-dicarboxylphenyl)benozoic acid

Abstract: Five 3D CPs were constructed from a designed π-conjugated aromatic pentacarboxylate with diverse structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(19 citation statements)
references
References 64 publications
1
18
0
Order By: Relevance
“…The sensing abilities of 1•4H 2 O•DMAC for Cr 2 O 7 2− , CrO 4 2− and MnO 4 − are comparable with these of the documented MOFs. [ 21–30 ] For example, {[Cd(L)(BPDC)]·2H 2 O} n and {[Cd(L)(SDBA)(H 2 O)]·0.5H 2 O} n [L = 4,4′‐ (2,5‐bis (methylthio)‐1,4‐phenylene)dipyridine, H 2 BPDC = 4,4′‐biphenyldicarboxylic acid, H 2 SDBA = 4,4′‐sulfonyldibenzoic acid] showed the K sv of 6.4 × 10 3 M −1 and 4.97 × 10 3 M −1 for Cr 2 O 7 2− , the detection limit of 37.6 μM and 48 μM, respectively. [ 21 ] {[Cd (IPA)(L)]} n (H 2 IPA = isophthalic acid, L = 3‐pyridylcarboxaldehyde nicotinoylhydrazone) exhibited the K sv of 2.91 × 10 3 M −1 , and the detection limit of 2.26 μM for Cr 2 O 7 2− , the K sv of 1.30 × 10 3 M −1 and the detection limit of 2.52 μM for CrO 4 2−.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The sensing abilities of 1•4H 2 O•DMAC for Cr 2 O 7 2− , CrO 4 2− and MnO 4 − are comparable with these of the documented MOFs. [ 21–30 ] For example, {[Cd(L)(BPDC)]·2H 2 O} n and {[Cd(L)(SDBA)(H 2 O)]·0.5H 2 O} n [L = 4,4′‐ (2,5‐bis (methylthio)‐1,4‐phenylene)dipyridine, H 2 BPDC = 4,4′‐biphenyldicarboxylic acid, H 2 SDBA = 4,4′‐sulfonyldibenzoic acid] showed the K sv of 6.4 × 10 3 M −1 and 4.97 × 10 3 M −1 for Cr 2 O 7 2− , the detection limit of 37.6 μM and 48 μM, respectively. [ 21 ] {[Cd (IPA)(L)]} n (H 2 IPA = isophthalic acid, L = 3‐pyridylcarboxaldehyde nicotinoylhydrazone) exhibited the K sv of 2.91 × 10 3 M −1 , and the detection limit of 2.26 μM for Cr 2 O 7 2− , the K sv of 1.30 × 10 3 M −1 and the detection limit of 2.52 μM for CrO 4 2−.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the quenching mechanism of 1•4H 2 O•DMAC for Cr 2 O 7 2− , CrO 4 2− , MnO 4 − and Fe 3+ can be assumed to the energy‐transfer. [ 9–15,21–30 ] However, no overlap between the UV–visible absorption spectra of Cu 2+ , Ag + and other ions with the excitation and emission spectra of 1•4H 2 O•DMAC . N1s X‐ray photoelectron spectroscopy (XPS) studies showed that the N1s peaks from triazole nitrogen atoms in 1•4H 2 O•DMAC were at 399.8, 401.8 and 405.2 eV (Figure 13).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, coordination polymers (CPs) as a family of molecular materials have attracted increasing attention and become one of the most promising research areas due to their fascinating topologies and versatile functionalities in, for example, gas adsorption, the catalytic degradation of organic dyes, hydrogen storage, sensor applications, separation applications and other areas (Cui et al, 2012;Du et al, 2014;Fan et al, 2018Gagnon et al, 2012;Zhang et al, 2014Zhang et al, , 2019Zou et al, 2014). It is well known that the various structures and properties of CPs can be affected by many factors, including temperature, solvent systems, pH, choice of organic ligands and types of metal ions (Lv et al, 2017;Wu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%